2012
DOI: 10.1186/1756-0500-5-170
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of horizontal transfer of feed introduced DNA to the aerobic microbiota of the gastrointestinal tract of rats

Abstract: Background Horizontal gene transfer through natural transformation of members of the microbiota of the lower gastrointestinal tract (GIT) of mammals has not yet been described. Insufficient DNA sequence similarity for homologous recombination to occur has been identified as the major barrier to interspecies transfer of chromosomal DNA in bacteria. In this study we determined if regions of high DNA similarity between the genomes of the indigenous bacteria in the GIT of rats and feed introduced DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…12 Mechanisms such as conjugation, transformation, and transduction can cause the transfer of antibiotic resistance genes and the spread of ARGs in the gut microbiome. 103 In transformation, naked DNA which might have antibiotic resistance genes is taken up by a bacterium. 103 During conjugative transfer, resistance genes could spread after the formation of a mating bridge between two cells.…”
Section: Adverse Effects Of Antibiotics On the Healthy Gut Microbiomementioning
confidence: 99%
See 2 more Smart Citations
“…12 Mechanisms such as conjugation, transformation, and transduction can cause the transfer of antibiotic resistance genes and the spread of ARGs in the gut microbiome. 103 In transformation, naked DNA which might have antibiotic resistance genes is taken up by a bacterium. 103 During conjugative transfer, resistance genes could spread after the formation of a mating bridge between two cells.…”
Section: Adverse Effects Of Antibiotics On the Healthy Gut Microbiomementioning
confidence: 99%
“…103 In transformation, naked DNA which might have antibiotic resistance genes is taken up by a bacterium. 103 During conjugative transfer, resistance genes could spread after the formation of a mating bridge between two cells. In this process, plasmids or conjugative transposons will move from a donor cell to a recipient.…”
Section: Adverse Effects Of Antibiotics On the Healthy Gut Microbiomementioning
confidence: 99%
See 1 more Smart Citation
“…72 Additional information April 2012April . 2002EFSA, 2009), but competence development and transformation of bacteria by genomic DNA of plants has not been observed in the lower gastrointestinal tract even with optimised model systems providing a selective advantage (Nordgård et al, 2007;Rizzi et al, 2008;EFSA, 2009;Nordgård et al, 2012). Furthermore, not all species have the same degree of competence.…”
Section: (Ii) Bacterial Dna Uptake and Stabilisationmentioning
confidence: 99%
“…Some studies have shown that introduced bacteria can be transformed naturally in the oral cavity of humans and animals (see Andersen et al, 2001;Hay et al, 71 The indicated uses of kanamycin or neomycin or similar substances include: gut irrigation; the treatment of encephalopathy in humans (neomycin); treatment of diarrhoea in farm animals; and aerosol administration for respiratory infections in humans and animals (EFSA, 2009 (Nordgård et al, 2007;Rizzi et al, 2008;EFSA, 2009;Nordgård et al, 2012). Furthermore, not all species have the same degree of competence.…”
Section: (I) Exposure To Dnamentioning
confidence: 99%